The Criminal Law Enforcement Based on Socio-Legal Approach Against Illegal Parking Officers in Achieving Justice - Badaru, Baharuddin; Ildar Begishev (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
This research aims to analyze aspects of law enforcement based on a socio-legal approach towards illegal parking officers in realizing justice. This research is socio-legal legal research which looks at law comprehensively including its relationship to non-legal aspects. The research results confirm that the factors related to the phenomenon of illegal parking officers are actually complex, including economic, social, cultural and political factors. The existence of illegal parking officers generally occurs because both regulations and law enforcement officers in Indonesia have not been optimal and effective in carrying out law enforcement efforts against illegal parking officers. The concept of criminal law enforcement against illegal parking officers based on a socio-legal approach can also prioritize non-penal and penal efforts so that it is hoped that the criminal law enforcement process can be carried out optimally. Efforts to enforce criminal law for illegal parking officers in realizing justice can be carried out by approaching legal and non-legal aspects in both preventive and repressive law enforcement.